2011
DOI: 10.1017/s0962728600002943
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a stray voltage threshold in Holstein heifers, influence of predictability and past experience on behavioural and physiological responses

Abstract: Stray voltage (< 10 V) may impair animal welfare. Our objectives were to: i) determine the threshold at which heifers react to voltage and ii) investigate effects of past experience and random applications of voltage. Firstly, forty heifers were trained to eat from two metallic feeders at the end of a test corridor. For 20 heifers, voltage was applied for 2 min (every day in steps of 0.33 V, 0 to 5 V) to the feeder (F1) in which the heifer started to eat (VOLT). Heifers could change to the non-electrified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…A meta-analysis based on 22 publications demonstrated that the perception threshold ranges between 2 and 8 mA [18] for a frequency of 50/60 Hz, with initial behavioral reactions typically occurring around 3 mA. Similar results were obtained in a subsequent study on heifers [19].…”
Section: Introductionsupporting
confidence: 67%
“…A meta-analysis based on 22 publications demonstrated that the perception threshold ranges between 2 and 8 mA [18] for a frequency of 50/60 Hz, with initial behavioral reactions typically occurring around 3 mA. Similar results were obtained in a subsequent study on heifers [19].…”
Section: Introductionsupporting
confidence: 67%